Strong Laws of Large Numbers for Arrays of Rowwise NA and LNQD Random Variables - Jiangfeng Wang; Qunying Wu (Journal of Probability and Statistics)
Some strong laws of large numbers and strong convergence properties for arrays of rowwise negatively associated and linearly negative quadrant dependent random variables are obtained. The results obtained not only generalize the result of Hu and Taylor to negatively associated and linearly negative quadrant dependent random variables, but also improve it.